EFFECT OF TIME OF SOWING ON GROWTH, YIELD AND ECONOMICS OF RABI PIGEONPEA [Cajanus cajan (L.) Millsp.] UNDER VARIED NUTRIENT LEVELS AND FOLIAR APPLICATION - M.V.S. NAIDU, C. NAGAMANI, V. SUMATHI, G. PRABHAKARA REDDY, P.SUDHAKAR and (The Journal of Research, PJTSAU, 2019)
A field experiment was conducted during rabi, 2012-13 and 2013-14 at dryland farm of S. V. Agricultural College, ANGRAU, Tirupati (A.P) to study the effect of time of sowing, nutrient levels and foliar application. The experiment consisted of three dates of sowing (II FN of September, I FN of October and II FN of October) as main plots, three nutrient levels (10-40-0, 20-50-10 and 30-60-20 kg N, P2O5 and K2O ha-1 respectively) as sub-plots and two foliar applications, NAA @ 25 ppm and DAP @ 2 % applied once at 60 DAS and twice at 60 and 80 DAS as sub-sub plots and replicated thrice in a split-split design. Significant improvement in the growth parameters (plant height, leaf area and dry matter production), yield and economics of rabi pigeonpea was observed with the crop sown during II FN of September. Among the nutrient levels tested, 30-60-20 kg N, P2O5 and K2O ha-1 resulted in higher growth parameters, yield and economics of rabi pigeonpea than other levels. Application of NAA (25 ppm) and DAP (2 %) applied twice at 60 and 80 DAS resulted in higher growth parameters, yield and economics than single spray at 60 DAS. The study revealed that early sown crop during II FN of September receiving a nutrient dose of 30-60-20 kg N, P2O5 and K2O ha-1 along with foliar application of NAA (25 ppm) and DAP (2 %) twice at 60 and 80 DAS gave higher growth, yield and economics of rabi pigeonpea.